2015
DOI: 10.7763/ijiet.2015.v5.484
|View full text |Cite
|
Sign up to set email alerts
|

Using iPad to Facilitate English Vocabulary Learning

Abstract: Abstract-With the development of new technologies, such as Web pages, Apps or social network, the language learning environment seems to be more multiple and interesting. The aim of this paper is to use iPad App in a Taiwanese classroom to help students' English vocabulary acquisition. During the 18-week lecture, the instructor chose two freshman English classes with a total of 74 students in a private university in Taiwan to be the research subjects. The classes were divided into 2 groups, that is, the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 13 publications
(18 reference statements)
6
56
0
1
Order By: Relevance
“…The findings of the present study are supported by Wang, Teng and Chen (2015) who explored the influence of iPad, a word power application, on learners' vocabulary knowledge. They found that those who exploited this software had better improvement in their vocabulary knowledge over those who did not use it.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings of the present study are supported by Wang, Teng and Chen (2015) who explored the influence of iPad, a word power application, on learners' vocabulary knowledge. They found that those who exploited this software had better improvement in their vocabulary knowledge over those who did not use it.…”
Section: Discussionsupporting
confidence: 80%
“…Having conducted the study, the researchers came to the conclusion that textual glosses enhanced students' vocabulary knowledge in short term and increased the students' productive vocabulary. Wang, Teng, and Chen (2015) conducted a quasi-experimental study to investigate the effect of iPad App on students' English vocabulary acquisition in a Taiwanese classroom. To this end, two freshman English classes with a total of 74 students in a private university in Taiwan were chosen to be the research participants.…”
Section: International Studiesmentioning
confidence: 99%
“…Hirsh-Pasek et al (2015) suggested that touchscreen apps should be designed to promote active, engaged, meaningful, and social interactive learning. Studies have shown that the embodied touching and interactivity have significant effects on learning (Agostinho et al, 2015; Dubé and McEwen, 2015; Moser et al, 2015; Wang et al, 2015; Huber et al, 2016). The embodied cognition theory proposed that cognitive processes are rooted in the body’s interactions with the world, and cognition should be understood in the context of its relationship to a physical body that interacts with the world (Wilson, 2002; Shapiro, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are many Apps for vocabulary learning. Take the App called "WordPower" as an example, by combining sound and pictures in the process of English vocabulary learning, the App improves students' English vocabulary acquisition and enhances students' English learning motivation (6). Another App "SpellBoard" facilitates students to practice English spelling drill anytime and anywhere.…”
Section: App For English Learningmentioning
confidence: 99%